Hyothetical Learning Trajectory On Dilation Material Using Realistic Mathematics Education and Geogebra Media - Hardiyanto, Dwi; Nursyahidah, Farida; Albab, Irkham Ulil (Universitas Wiralodra, 2024)
Dilation is a part of geometry transformation that is useful for students. However, students often have difficulty in understanding dilation material. Therefore, this study aims to develop a learning trajectory to facilitate students in understanding dilation material by using the context of Tedhak Siten tradition. The research subjects consisted of 32 ninth grade students of SMP Negeri 6 Semarang, which was conducted from August to September 2023. The research method used is design research which consists of three stages, namely preparing for experiment, design experiment, and retrospective analysis. All learning activities were based on the Realistic Mathematics Education approach and supported by GeoGebra media. The results of this study include three learning activities, including: observing the Tedhak Siten tradition video to find the properties and definition of dilation, finding the formula and results of dilation, and solving contextual problems related to dilation. From the activities carried out, it can be seen that learning dilation by using the context of the Tedhak Siten tradition based on RME and supported by GeoGebra media can help students improve their understanding of the concept of dilation material in class IX SMP Negeri 6 Semarang. In addition, Tedhak Siten tradition can be used as a relevant context in learning mathematics.